Produção e separação de diacilglicerol a partir dotriacilglicerol do óleo de palma - Voll, Fernando Augusto Pedersen (2011)
Palm oil ranks first in world production of edible oils. Its unique composition of about 50% in saturated fatty acids gives good consistency at room temperature, however, for presenting this large amount of saturated fatty acids, this oil has received a negative perception from the consumers. In this context there is interest in the production of a palm oil rich in diacylglycerol molecules, which exhibit characteristics such as flavor and appearance similar to those of triacylglycerol. Studies indicate that consumption of diacylglycerol can avoid problems that are related to the high consumption of triglycerides, such as obesity and cardiovascular diseases. This study aims to evaluate the kinetics of enzymatic hydrolysis of palm oil and the thermodynamics of phase equilibrium between the hydrolysis products with water and ethanol, which enables simulation of processes which aim to achieve a palm oil that is rich in diacylglycerol. The partial hydrolysis of palm oil was carried out in a solvent-free medium at 55 °C, 400 rpm, with the immobilized enzyme Lipozyme RM IM. The variables evaluated in the system were: enzyme concentration, initial water concentration and reaction time. A palm oil with 35.91 wt% in DAG was obtained for the best conditions predicted by the kinetic model: 2.87 wt% enzyme/substrate, 2.10 wt% water/oil and 72 hours of reaction. The study of the liquid-liquid equilibrium of palm oil (obtained in the hydrolysis step) with ethanol and water was used to estimate UNIQUAC parameters, which were used in the simulation of a liquid-liquid extraction process for the purification of DAG. The phases split at each extraction stage were calculated by minimizing the Gibbs free energy of the system. The simulations of liquid-liquid extraction indicated the possibility of obtaining a palm oil with 87.64 wt% in DAG and 0.53 wt% of acidity.